Adaptor protein regulation of T-lymphocyte migration - Lim, Carey Fang Hui (2015)
T-lymphocyte migration is central to the adaptive immune response, which is dependent mainly on the integrin LFA-1-mediated signalling. LFA-1 interacts with its ligand ICAM-1 (expressed on endothelium) and this interaction triggers cytoskeletal rearrangement and T-cell motility. Centrosome and Golgi localized Protein Kinase N- Associated Protein (CG-NAP) is an adaptor protein and plays a multifunctional role in facilitating signal transduction processes. However, the mechanistic role of CG-NAP in T-lymphocyte migration is not clear. [4th Award]